Hubungan Antara Tingkat Pengetahuan Dengan Pencegahan Kekambuhan Pada Klien Dermatitis Kontak Di Poliklinik Kulit Rumah Sakit X - Erlawati, Ni Desak Putu Erlawati; Made Rismawan; I G.A. Rai Rahayuni (Jurnal Riset Media Keperawatan, 2023)
Contact dermatitis is the most common type of dermatitis found in all skin diseases. Efforts to prevent recurrence of contact dermatitis require good understanding and knowledge because it can influence a person's mindset by knowing the dangers of dermatitis to take preventive action. This study aims to determine the relationship between the level of knowledge and prevention of recurrence in contact dermatitis clients at the Dermatology Polyclinic Hospital X. This type of research is descriptive correlational with a cross-sectional design. The research sample was 150 contact dermatitis clients. The sample collection technique used the consecutive sampling technique. Data were collected using a questionnaire regarding knowledge and prevention of recurrence of contact dermatitis. Data were analyzed with the Spearman Rank test. The results showed that most of the respondents had insufficient knowledge about contact dermatitis, namely 75 respondents (50%) and prevention of recurrence of the appearance of contact dermatitis, namely 69 people (46%). The results of the Spearman Rank test showed that there was a relationship between the level of knowledge and the prevention of recurrence in contact dermatitis clients with p=0.001 and a very strong correlation and a positive direction of correlation (r=0.776). Knowledge about prevention of contact dermatitis can improve behavior to prevent recurrence of the disease.